Female and male bodies in the Middle Ages: a study of the qualifying adjectives in the lais of Marie de France (1160-1210) - Silva, Samara Araújo da; Xypas, Rosiane (The ESPecialist, 2024)
Studies of French Literature are essential for broad teacher training. But for those of language too. Understanding qualifying adjectives seen as the expression of the quality of reality designated by the noun, arises the question: "what is the function of qualifying adjectives related to the theme of the representation of female and male bodies in the Middle Ages?" The objective of this study was to delve deeper into the use and context of the word body in twelve literary texts. Results indicate that adjectives are epithet modifiers, characterizing, specifying or modulating the semantics of the studied noun, and that the female body was valued over the male body.